Pembinaan Keagamaan Lansia di Panti Sosial Tresna Werdha Budi Sejahtera - Siti Rahmah (Alhadharah: Jurnal Ilmu Dakwah, 2017)
This study discusses the religious guidance of the elderly in PSTW Budi Sejahtera house South Kalimantan, and its supporting and inhibiting factors. Research results show that: (1) the religious guidance in the house is the process of guiding the elderly, (2) the activity of religious guidance of the elderly in the house includes mental guidance, reading yasin, tahlil and shalawat rituals, are adequate in terms of quantity but not of quality, (3) inhibiting factors are the age of the elderly causing a lack of physical ability and memory, inadequate educational background, and mental disorder, especially among the elderly with social problems